PENGARUH CUSTOMER SATISFACTION DAN CORPORATE REPUTATION TERHADAP LOYALITAS PASIEN PADA RUMAH SAKIT BHAYANGKARA KEDIRI - Singgih Adhi Akma; Sri Wahyuni Mega H; Lina Saptaria (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
This research aims to determine the influence of customer satisfaction and corporate reputation on patient loyalty at Bhayangkara Kediri Hospital. The variables in this research are Customer Satisfaction (X1), Corporate Reputation (X2), and Patient Loyalty (Y). This research uses quantitative methods using data collection techniques in the form of interviews, observations, literature studies and questionnaires. Meanwhile, the analysis used is validity test, reliability test, classical assumption test, multiple linear regression test, t test and f test and coefficient of determination. Sampling in this study used purposive sampling taking into consideration that there were 70 patients at Bhayangkara Kediri Hospital based on the results of the research conducted. The results of this study used the SPSS 25.0 program using a significant level of 5% or 0.05 with the results (1) The results of the calculation of the t test on the first hypothesis obtained a calculated t value of 6.091 with a significance value of 0.013 <0.05. These results indicate that Ha is accepted and Ho is rejected, meaning that there is an influence between customer satisfaction variables on patient loyalty partially. (2) The results of the calculation of the t test on the second hypothesis obtained a t value of 5.801 with a significance value of 0.047 <0.05. These results indicate that Ha is rejected and Ho is rejected, meaning that there is no effect between corporate reputation variables on patient loyalty partially. (3) The results of calculating the calculated F value in this study amounted to 30.009 and the significance value of F was 0.000 which was <0.05. It can be concluded that Ha is accepted and Ho is rejected, which means that simultaneously customer satisfaction and corporate reputation have a significant effect on patient loyalty at Bhayangkara Hospital Kediri, these results prove that empirically the third hypothesis can be proven.